(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Egg parasitoids and egg parasitism were studied in 32 egg batches of the pine processionary moth collected near Korca/ Albania in heights of 1050-1400 m in August-September 1997, after caterpillars’ hatch. In this mountainous region, Baryscapus servadeii (Dom.) was most abundant at the higher level, followed by Ooencyrtus pityocampae (Mercet) at the lower level. Trichogramma sp. was only found at 1400 m a.s.l. Additionally, the hyper-parasitoid Baryscapus transversalis Graham was established parasitizing dominantly the eggs placed near the beginning and the end of the batches. The grade of parasitism of the various egg batches varied from zero to 61 %. The emergence dynamics of the parasitoids showed a peak of B. transversalis in November of the year, in which the host eggs were layed. B. servadeii emerged mainly in J anuary of the following year. A high percentage of egg parasitoids died in the eggs, mainly from O. pityocampae and the polyembryonic Trichogramma sp. (see also Tsankov et al., 1996a); up to 12 pupae were found in one egg.